Students’ Perceptions of the Role of Various Players in Agricultural Technologies and Innovations Development - Ayisi-Nyarko, Daniel; Masambuka-kanchewa, Fallys; Obaa, Bernard (Journal of Agricultural Studies, 2024)
Technologies and innovations have revolutionized the agricultural industry throughout time; as more technologies and innovations keep gaining prominence in the agricultural industry, there is an increasing divergence of views on their origin, creators, and meaning among scholars across the scientific fields. Students in agricultural programs emerge from different fields in the agricultural disciplines; as a result, they have different exposure and experience with different technologies and innovations. Their varied backgrounds influence how they define, explain, and conceptualize technologies and innovations in agriculture, giving rise to varied perceptions of who should be recognized and who should not. The present study sought to explore agricultural students’ perceptions of technologies and innovations and the role of farmers and extension agents in their development. The study adopted a qualitative content analysis approach by analyzing the views expressed by seventeen students from two different universities. The results showed that agricultural students have varied perceptions of what technologies and innovations represent in agriculture. Most of the students perceived technology as equipment and tools, and innovation as improved techniques and as a discovery of new methods. They also had conflicting views on the role played by the farmers, extension agents, and researchers in technology and innovation development. While the majority viewed farmers as adaptors of technologies and innovations, none viewed extension agents as contributors to technologies and innovation development rather than as disseminators. Our findings suggest a lack of knowledge in the collective role played by farmers, extension agents, and scientists in technology and innovation development. The repercussion of this is that it may contribute towards limited inclusion of diverse perspectives in technology and innovation creation and dissemination, which may affect sustainable agricultural development.